Black Death Land Abandonment Drove European Diversity Losses - Jonathan D. Gordon; Brennen Fagan; Jonathan Finch; Lindsey Gillson; Nicky Milner; Chris D. Thomas (Ecology Letters, 2026)
The current prevailing perception is that human impacts on the biological realm have been overwhelmingly negative. Here, we test this narrative by considering the consequences for aspects of floristic diversity of the ‘Black Death era’ (1300–1400 ce ), where one third of Europe's population died within half a decade. Based on evidence from 109 pollen records spanning the Common Era, we find increasing floristic diversity from 0 to ~1300 ce as human populations increased, followed by rapid and substantial diversity reductions during the famine‐ and disease‐driven human mortality events of the ‘Black Death era’. As human populations recovered following the mortality shock, diversity also recovered. Strikingly, it was landscapes characterized by cereal cultivation that generated both the overall Common Era increases and the Black Death era declines in diversity. The highest diversity levels were achieved in human‐generated, mosaic landscapes, highlighting the integral role of human action in biodiverse European landscapes.

Increased Holocene Diversity in Europe Linked to Human‐Associated Vegetation Change - Jonathan D. Gordon; Brennen Fagan; Esther Githumbi; Nicky Milner; Chris D. Thomas (Global Ecology and Biogeography, 2025)
Aim It is widely reported that aspects of present‐day global biodiversity are declining, with humans largely to blame. However—perhaps paradoxically—in Europe, floristic diversity and human populations have grown in tandem for millennia. Disturbance intensity and habitat heterogeneity potentially explain this phenomenon, though we lack understanding of how human land use intensity affected biodiversity at numerous spatial scales over the Holocene. Here, we examine the relationships between anthropogenic vegetation change and floristic diversity over the last 12 millennia in Europe, at multiple spatial scales. Location Europe. Time Period The Holocene (11,700–100 cal yr BP). Major Taxa Studied Plants. Methods We examined the spatio‐temporal dynamics of, and relationships between, floristic richness, evenness and compositional turnover with an index of anthropogenic vegetation change since 11,700 cal yr. BP, analysing 7853 pollen samples from 213 records (sites). We evaluated how changes to the proportional site occupancies of human‐associated and other taxa related to diversity patterns. Results (1) Floristic richness, evenness, and compositional turnover increased from 9000 years ago to 1850 CE. (2) Temporal increases in richness and evenness were positively associated with the anthropogenic vegetation index in the majority of vegetation zones and sites, whereas compositional turnover was only associated with the anthropogenic index at the site level. (3) Holocene site occupancies of all human‐associated taxa were positively associated with biodiversity gains, whereas the results for other taxa (that were not associated with people) were mixed. Main Conclusions Following the onset of warmer Holocene conditions, floristic diversity initially declined, while subsequent increases were positively associated with human impacts over the vast majority of Europe. From the mid‐Holocene onwards, farming populations increasingly disturbed European landscapes—perhaps replicating the now‐lost megafaunal disturbance regimes—to produce patchy and increasingly diverse vegetative communities, the legacies of which are still present today.

Marine exploitation and the arrival of farming: resolving the paradox of the Mesolithic-Neolithic transition in Denmark - T. Rowan McLaughlin; Harry K. Robson; Rikke Maring; Adam Boethius; Eric Guiry; Daniel Groß; Satu Koivisto; Bente Philippsen; Nicky Milner; Geoff Bailey; Oliver E. Craig (Quaternary Science Reviews, 2025)

Destructive events and the impact of climate change on Stone Age coastal archaeology in North West Europe: past, present and future - Nicky Milner (Journal of Coastal Conservation, 2012)